2016
DOI: 10.1007/s00210-016-1230-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pregabalin on contextual memory deficits and inflammatory state-related protein expression in streptozotocin-induced diabetic mice

Abstract: Diabetes mellitus is a metabolic disease characterized by hyperglycemia due to defects in insulin secretion or its action. Complications from long-term diabetes consist of numerous biochemical, molecular, and functional tissue alterations, including inflammation, oxidative stress, and neuropathic pain. There is also a link between diabetes mellitus and vascular dementia or Alzheimer’s disease. Hence, it is important to treat diabetic complications using drugs which do not aggravate symptoms induced by the dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 70 publications
(109 reference statements)
1
10
0
Order By: Relevance
“…Glucose transporters have also been identified at the BBB endothelial cells; GLUT3 (Gerhart, Broderius, Borson, & Drewes, ; Shawahna et al, ), GLUT4 (Ngarmukos, Baur, & Kumagai, ), SGLT1 (Nishizaki & Matsuoka, ; Yamazaki, Ogihara, Harada, & Tokuyama, ), and SGLT2 (Enerson & Drewes, ; Jurcovicova, ) have been reported in lower levels. Insulin sensitive GLUT4 expression has also been shown to be at the BBB of the ventromedial hypothalamus indicating its role in brain sensing of blood glucose levels (Keeney et al, ; Ngarmukos et al, ; Patel, Gupta, & Udayabanu, ; Sałat et al, ). Neurons mainly express GLUT3, a high “affinity” and high capacity glucose transporter in comparison with GLUT1 (Maher, Davies‐Hill, & Simpson, ; Simpson, Carruthers, & Vannucci, ).…”
Section: Alzheimer Diseasementioning
confidence: 99%
“…Glucose transporters have also been identified at the BBB endothelial cells; GLUT3 (Gerhart, Broderius, Borson, & Drewes, ; Shawahna et al, ), GLUT4 (Ngarmukos, Baur, & Kumagai, ), SGLT1 (Nishizaki & Matsuoka, ; Yamazaki, Ogihara, Harada, & Tokuyama, ), and SGLT2 (Enerson & Drewes, ; Jurcovicova, ) have been reported in lower levels. Insulin sensitive GLUT4 expression has also been shown to be at the BBB of the ventromedial hypothalamus indicating its role in brain sensing of blood glucose levels (Keeney et al, ; Ngarmukos et al, ; Patel, Gupta, & Udayabanu, ; Sałat et al, ). Neurons mainly express GLUT3, a high “affinity” and high capacity glucose transporter in comparison with GLUT1 (Maher, Davies‐Hill, & Simpson, ; Simpson, Carruthers, & Vannucci, ).…”
Section: Alzheimer Diseasementioning
confidence: 99%
“…Thus, it could be assumed that SCOP may alleviate contextual fear. On the other hand, the SCOP-injected group was the only one that presented a strong prolongation of grooming time, which might be a manifestation of increased stress and anxiety (Kalueff and Tuohimaa 2005 ; Sałat et al 2016 ). These data remain apparently inconsistent, i.e., SCOP in the same test reduced contextual fear measured as freezing behavior and enhanced self-grooming that is usually associated with stress.…”
Section: Discussionmentioning
confidence: 99%
“…These valuable research tools enable to study various types of memory (Fig. 1 ) (Blaser and Heyser 2015 ; Cho et al 1999 ; Frankland et al 1998 ; Malikowska et al 2017 ; Podkowa et al 2016 ; Sałat et al 2016 ; Stiedl et al 2000 ; Sunyer et al 2007 ).
Fig.
…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that although several studies used this measure of behavioral depression induced by pain, other reports showed that ambulatory locomotion in rodents did not decrease (or did so only minimally) in a variety of pain models such as CFA-induced inflammatory pain, prostatitis, ovariectomy-induced osteoporosis, diabetic neuropathy, or spared nerve injury, even in animals that displayed marked sensory hypersensitivity (e.g. Urban et al, 2011;Tékus et al, 2014;Schwartz et al, 2015;Zhou et al, 2015;Sałat et al, 2016;Montilla-García et al, 2017;Suzuki et al, 2018). The quantification of vertical activity may be more sensitive than ambulatory locomotion in detecting pain-induced alterations, in particular in pain models affecting the hindlimbs; this is exemplified in studies of monoiodoacetate-induced osteoarthritis or plantar incision (e.g.…”
Section: Pain Interference In Exploratory Locomotion In a Novel Envirmentioning
confidence: 99%